DRUG PRESCRIPTION PATTERN OF BREAST CANCER PATIENTS IN A TERTIARY CARE HOSPITAL IN WEST BENGAL: A CROSS-SECTIONAL AND QUESTIONNAIRE-BASED STUDY - Adhikari, Anjan; Chakraborty, Dipesh; Indu, Rania; Bhattacharya, Sangita; Ray, Moumita; Mukherjee, Ramanuj (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Â Objective: Cancer is a disease of uncontrolled division of cells in any part of the body. Breast cancer most common in women accounts for 13% of the death worldwide. The objective of the present study was to evaluate the drug prescription pattern of breast carcinoma patients in a tertiary care hospital of West Bengal. Methods: This was a cross-sectional observational questionnaire-based study done for a period of 6 months at the Department of Pharmacology in Collaboration with the Department of Surgery and Department of Radiotherapy of a Tertiary Care Hospital at Kolkata, West Bengal, India. Female patients with breast cancer (originated from epithelial tissues) of different types and grade attending surgery outdoor patient department were taken as subjects for the study, after signing informed consent. Results: The present study evaluated 28 patients (n=28) diagnosed as breast cancer by the physicians of the department of surgery and radiotherapy. It was observed that breast cancer was mostly found in the middle age group. Breast carcinoma in postmenopausal women accounted to 75%. The most prevalent breast cancer was invasive ductal carcinoma, accounting to 75% of the study population. 5-Fluorouracil, epirubicin, doxorubicin, cyclophosphamide, docetaxel/paclitaxel, and carboplatin were mostly used as chemotherapeutic agent. Conclusion: Breast carcinoma being a prevalent type of cancer in females, the present study tried to evaluate the pattern of prescribing chemotherapeutic agents for breast cancer patients in a tertiary care hospital. Such study is essential to evaluate and refine the therapeutic regimen of the cancer patients to reduce their sufferings.